Experimental study and finite element analysis on impact resistance of large-rupture-strain FRP reinforced civil air defense wall. (July 2022) - Shi, Chenglong; Zhang, Jigang; Zhang, Junbo; Zhang, Menglin; Yan, Qingfeng; Zhao, Yang; Yang, Yingchun; Shao, Feng
Abstract: In order to study the impact resistance of civil air defense wall strengthened with large-rupture-strain FRP and improve its explosion resistance, the pendulum impact test and ANSYS/LS-DYNA finite element simulation were used to study the influence of the reinforcement area, pendulum impact height and impact times of large-rupture-strain FRP on the impact resistance of civil air defense wall. Large-rupture-strain FRP is a new type of fiber reinforced plastics, which has the advantages of large tensile fracture strain and high strength. It is pasted on the back of the civil air defense wall to improve the overall ductility and flexural stiffness of the civil air defense wall. In this paper, large-rupture-strain FRP is firstly applied to the reinforcement of civil air defense wall resist out-of-plane impact load to improve the impact resistance of civil air defense wall. The advantages of large-rupture- strain FRP reinforcement of civil air defense wall to improve the impact resistance are analyzed from the parameters of civil air defense wall damage degree, mid-span horizontal maximum displacement and residual displacement, concrete cracks and steel strain. The pendulum impact test results show that the civil air defense wall bonded with large-rupture-strain FRP can well coordinate with the wall, restrain the cracking of the back concrete, and avoid the overall collapse of the civil air defense wall due to local damage. The residual displacement is significantly reduced, and the crack width of the concrete is reduced by 25%–76%. Even if the civil air defense wall is subjected to multiple impacts, there is no fracture of large-rupture-strain FRP. The large-rupture-strain FRP can still play a role in strengthening and restrain the stripping of the back concrete fragments. The advantage of large tensile fracture strain of large-rupture-strain FRP makes up for the shortcomings of small tensile fracture strain of FRP commonly used at present, and finally provides a new reinforcement material for improving the explosion resistance of civil air defense wall.